The Development of News Text-Based Problems Teaching Materials in 12th Grade Students of Vocational High School at TR Sinar Husni of 2019/2020 - Bobby Pratama Putra; Khairil Ansari; Isda Pramuniati (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research aims to develop the material teaching of News text based Problem in 12th grade Students of Vocational High School at TR Sinar Husni. The methods used is quantitative method. It also use random sampling system. The product that was developed was in the form of a problem-based module on writing news text material entitled "News Text -Based Problem" for 12th grade students of Vocational High School at TR Sinar Husni qualified and suitable for use as individual teaching materials based on the assessment of material experts and learning design experts. The feasibility of teaching materials by material experts included in the criteria is excellent with aspects of the feasibility of the contents of 90.1%, the feasibility of the presentation of 90.3%, and the feasibility of aspects of the language of 93.2%. The feasibility of the design by the design experts in the criteria is excellent with an average score of 89.5%, the module size aspect with an average score of 89%, the module cover design (cover) with an average score of 91.6%, and the module design with an average score of 87.5%. The student news text test results after using the news text module increased by 9.47, with an average pretest learning outcomes or before using the module of 76.07 while the posttest learning outcomes or after using the module amounted to 85.54.